An illustrated key for identification of colour aberrations in alcids with a revision of nomenclature used - K. Cieślińska; P. Bodson; E. Gruber; K. Piening; M. Syposz; K. Wojczulanis-Jakubas; D. Jakubas (The European Zoological Journal)
Colour aberrations of plumage or bare parts of the body have been described in many avian taxa but their frequency in populations is low. In recent years, due to the development of cameras and the ability to share observations via social media, reports on observations of aberrantly coloured birds have become more common even in groups of birds breeding in less accessible sites, such as seabirds. In this study we review colour aberrations of integumentary structures (plumage and bare parts: beak, eye iris, legs) in a group of pelagic seabirds, alcids. To illustrate particular aberrations, we used our own photographs and conducted searches for similar images online and in published papers. In total, we collected 82 cases of unusually coloured individuals of nine alcid species. We revised the types of aberrations described in collected material in accordance with the recently proposed classification and terminology, and found that only 25.6% of cases were properly classified. The most commonly misused term for observed aberrations in collected images was “leucism” (34.1% of cases), which usually would have been more accurately described as Brown, Ino, Progressive Greying, rather than true Leucism. We also found that Progressive Greying (37.8%) and Brown (19.5%) were the most frequently recorded colour aberrations in the studied group. Our synthesis offers an updated summary of the colour plumage aberrations in alcids and a practical tool for identification of various colour aberrations in the group. It can help to classify the aberrations in future studies. Given that the frequency of colour aberrations may be indicative of an increased mutation rate or a high rate of inbreeding in a population, we encourage researchers to correctly identify and note those cases.